Data from: Mosquitoes cloak their legs to resist insecticides - Balabanidou, Vasileia (2019)
Malaria incidence has halved since the year 2000, with 80% of the reduction attributable to the use of insecticides. However, insecticide resistance is now widespread and is rapidly increasing in spectrum and intensity across Africa, and may be contributing to the increase of malaria incidence in 2018. The role of detoxification enzymes and target site mutations has been documented in the major malaria vector Anopheles gambiae, however, the emergence of striking resistant phenotypes, suggests the occurrence of additional mechanisms. By comparing legs, the most relevant insect tissue for insecticide uptake, we show that resistant mosquitoes largely remodel their leg cuticles via enhanced deposition of cuticular proteins and chitin, corroborating a leg-thickening phenotype. Moreover, we show that resistant female mosquitoes seal their leg cuticles with higher total and different relative amounts of cuticular hydrocarbons, compared to susceptible ones. The structural and functional alterations in Anopheles female mosquito legs are associated with a reduced uptake of insecticides, substantially contributing to the resistance phenotype.